Association between the rs1465040 single-nucleotide polymorphism close to the transient receptor potential subfamily C member 3 (TRPC3) gene and postoperative analgesic requirements - Yoshinori Aoki; Daisuke Nishizawa; Junko Hasegawa; Shinya Kasai; Kaori Yoshida; Yoshihiko Koukita; Tatsuya Ichinohe; Makoto Nagashima; Ryoji Katoh; Yasuo Satoh; Megumi Tagami; Masakazu Hayashida; et al. (Elsevier, 2015)
An association between postoperative analgesic requirements in subjects who underwent orthognathic surgery and the rs1465040 single-nucleotide polymorphism close to the transient receptor potential subfamily C member 3 (TRPC3) gene was suggested by our previous genome-wide association study. To verify this association, we analyzed the association between the rs1465040 SNP and analgesic requirements, including opioid requirements, after open abdominal surgery. The association between the rs1465040 SNP and postoperative analgesic requirements was confirmed in the open abdominal surgery group (P = 0.036), suggesting that the TRPC3 SNP may contribute to predicting postoperative analgesic requirements.